Irrigation as a source of drinking water: Is safe use possible? - Hoek, Wim van der; Konradsen, Flemming; Ensink, Jeroen H.J.; Mudasser, M.; Jensen, P.K. (2002)
Published in ?Tropical Medicine and International Health, Vol.6, No.1, pp.46-54, January 2001.? The complete article is available on the CD-ROM version of this Annual Report.